2006
DOI: 10.1111/j.1365-2958.2006.05406.x
|View full text |Cite
|
Sign up to set email alerts
|

The Group B Streptococcus NADH oxidase Nox‐2 is involved in fatty acid biosynthesis during aerobic growth and contributes to virulence

Abstract: SummaryNumerous Streptococcaceae produce an H2O-forming NADH oxidase, Nox-2, which has been generally implicated in aerobic survival. We examined the roles of Nox-2 in Group B Streptococcus (GBS), a leading agent of neonatal infections. While nox2 inactivation caused an aerobic growth arrest, no improvement was seen by addition of antioxidants to cultures, suggesting that this defect was not due to accumulation of toxic oxygen species. Using several approaches, we show that the observed inability of the nox2 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
70
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(73 citation statements)
references
References 58 publications
2
70
0
1
Order By: Relevance
“…In pathogenic streptococci that encounter oxygen upon host colonization, NADH oxidases contribute to oxygen tolerance by decreasing the intracellular NADH/NAD ratio and/or by direct elimination of oxygen (2,10,14,37,38). In L. lactis, which is particularly exposed to oxygen when it is used for milk fermentation in the dairy industry, the role of NADH oxidases in oxygen tolerance has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In pathogenic streptococci that encounter oxygen upon host colonization, NADH oxidases contribute to oxygen tolerance by decreasing the intracellular NADH/NAD ratio and/or by direct elimination of oxygen (2,10,14,37,38). In L. lactis, which is particularly exposed to oxygen when it is used for milk fermentation in the dairy industry, the role of NADH oxidases in oxygen tolerance has not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Their inactivation in several streptococci strongly reduces the aerobic growth. Inactivation of nox2 in Streptococcus pneumoniae and Streptococcus agalactiae reduces growth in aerated media by 80% (37,38). The growth defect of the S. agalactiae mutant has been attributed to a defect in fatty acid production resulting from nonproduction of the fatty acid precursor acetyl-coenzyme A (CoA) due to strictly homolactic fermentation (37).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…If not fully reduced by Nox, environmental oxygen can form toxic superoxide and H 2 O 2 . Strains of GBS and pneumococcus lacking Nox were unable to grow under vigorous agitation conditions and showed attenuated virulence in animal models (514,515). An E. faecium Tn917 transposon insertion mutant of nox showed a 98% reduction of NADH oxidase activity (516).…”
Section: Oxidative Stress and Virulencementioning
confidence: 99%
“…Our laboratory has previously shown that Nox is the major oxygen-metabolizing enzyme used by S. mutans, responsible for reduction of approximately 40% of the dissolved oxygen encountered in dental plaque, and that the Nox enzyme shows elevated activity under conditions of both oxidative stress and low pH (21). Mutation of nox in the genomic type strain, S. mutans UA159, has demonstrated that NADH oxidase plays a role in the acid stress response, as inactivation of nox invokes changes in membrane fatty acid composition and metabolic output reminiscent of those seen during exposure to low pH (21,(23)(24)(25). In addition to reducing oxygen, Nox is also critical in the regeneration of NAD ϩ , a key molecule in the production of pyruvate during carbon metabolism in streptococci (26)(27)(28)(29).…”
mentioning
confidence: 99%